DEVELOPMENT OF LEARNING DEVICES OF BASIC ELECTRONIC VIRTUAL LABORATORY BASED ON PSPICE SOFTWARE - Muchlas, Muchlas; Budiastuti, Pramudita (Universitas Ahmad Dahlan, 2020)
The availability of modules to support basic electronic practices based on virtual laboratories has not yet met the needs. The purpose of this development research is to produce basic electronic practice learning devices based on the PSPICE application program. The development procedure uses ADDIE (analysis, design, development, implementation, evaluation). ADDIE is used to direct the design process as specified. Product performance was tested using ongoing formative evaluation. The product feasibility test uses a comparative analysis of the results of the PSPICE experiment against the theory. The results show that all modules developed can display the same characteristics as their theoretical character. The results show that the modules have very good performance. Modules are suitable for use as a medium for basic electronic practice using PSPICE-based virtual laboratories. The products are in the form of electronic circuits with 31 schematic PSPICE formats. Product results to support basic electronic practices covering topics: capacitor filling and discharging, RC circuits, diode characteristics, wave forming circuits, rectifier circuits, voltage clamp, voltage circuits, transistor characteristics, and amplifier transistor.